Modelagem computacional de ventosas automáticas de duplo efeito com abertura e fechamento não instantâneos como mecanismo de alívio do golpe de aríete - Rodrigues, Marcus Vinícius Sousa (2008)
During time dependent phenomena in pipelines, very low pressures may occur, mostly in points of dow elevations. In these cases, air accumulated in these points is carried out by the water flow and may damage the pipeline. This also causes reduction of the flow area and consequently, reduction of the flow itself. The most modern Waterhammer protection devices and among them, we find the air entry valves, which is the object of this work. The boundary conditions for these devices is very complex and results in a non-linear equations. Besides, we have to consider that the air flow cross-section area of the valves orifice varies linearly with time. In order to solve this non-linearity it was used the method of parabolic approximation for solving the equation in each interval of subsonic air flow. In the present work, several Waterhammer pipeline simulations were performed in order to verify the performance of the double effect automatic air valves, with non-instantaneous closing. The UFC6 computer software were used to accomplish these simulations. Air valves are a satisfactory hydraulic solution for the Waterhammer problem since they are cheaper than other devices and easy to install and mountain.